Purification and partial characterization of a new mannose/glucose‐specific lectin from Dialium guineense Willd seeds that exhibits toxic effect. Issue 8 (19th June 2013) - Bari, Alfa U.; Silva, Helton C.; Silva, Mayara T. L.; Pereira Júnior, Francisco N.; Cajazeiras, João B.; Sampaio, Alexandre H.; Leal, Rodrigo B.; Teixeira, Edson H.; Rocha, Bruno A. M.; Nascimento, Kyria S.; Nagano, Celso S.; Cavada, Benildo S.
Abstract : A new mannose/glucose‐specific lectin, named DigL, was purified from seeds of Dialium guineense by a single step using a Sepharose 4b‐Mannose affinity chromatography column. DigL strongly agglutinated rabbit erythrocytes and was inhibited byd ‐mannose, d ‐glucose, and derived sugars, especially α‐methyl‐d ‐mannopyranoside and N ‐acetyl‐d ‐glucosamine. DigL has been shown to be a stable protein, maintaining its hemagglutinating activity after incubation at a wide range of temperature and pH values and after incubation with EDTA. DigL is a glycoprotein composite by approximately 2.9% of carbohydrates by weight. By sodium dodecyl sulfate polyacrylamide gel electrophoresis analysis, the purified DigL exhibited an electrophoretic profile consisting of a broad band of 28–30 kDa. Analysis using electrospray ionization mass spectrometry indicated that purified DigL possesses a molecular average mass of 28 452 ± 2 Da and shows the presence of possible glycoforms. In addition, DigL exhibited an intermediary toxic effect on Artemia sp. nauplii, and this effect was both dependent on native structure and mediated by a carbohydrate‐binding site. Copyright © 2013 John Wiley & Sons, Ltd. Abstract : A new mannose/glucose‐specific lectin, named DigL, was purified from seeds of Dialium guineense using a Sepharose 4b‐Mannose affinity chromatography column. DigL is a stable glycoprotein whit a molecular average mass of 28 452 ± 2 Da and shows the presence of possible glycoforms. In addition, DigL exhibited an intermediary toxic effect on Artemia sp. nauplii, and this effect was both dependent on native structure and mediated by a carbohydrate‐binding site.